2011
DOI: 10.1172/jci46311
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 expression on PD-1+ HCV-specific human CTLs is associated with viral persistence, and its blockade restores hepatocyte-directed in vitro cytotoxicity

Abstract: Tim-3 expression on PD-1 + HCV-specific human CTLs is associated with viral persistence, and its blockade restores hepatocytedirected in vitro cytotoxicity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 0 publications
3
54
0
Order By: Relevance
“…Further, we found the same pattern within the liver and peripheral blood and for CD4 (Th17) cells, underscoring the utility of CD161 as a phenotypic marker for IL-17 cells, irrespective of CD4 or CD8 lineage. We have recently proposed a hierarchal model of T exhaustion [18] in the liver that follows a pattern of progressive loss of function (decreased IFN-c and TNF-a production) and its association with dual expression of PD-1 and Tim-3. In the current study, we found that both Tim-3 and PD-1 were inversely correlated with IL-17 production, but this association was tissue-specific, i.e., demonstrable in the liver and not peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we found the same pattern within the liver and peripheral blood and for CD4 (Th17) cells, underscoring the utility of CD161 as a phenotypic marker for IL-17 cells, irrespective of CD4 or CD8 lineage. We have recently proposed a hierarchal model of T exhaustion [18] in the liver that follows a pattern of progressive loss of function (decreased IFN-c and TNF-a production) and its association with dual expression of PD-1 and Tim-3. In the current study, we found that both Tim-3 and PD-1 were inversely correlated with IL-17 production, but this association was tissue-specific, i.e., demonstrable in the liver and not peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…T cells within the liver; moreover, these cells are concentrated within the CD45RA-CD27?CCR7? central memory cell subset [18]. As shown in Fig.…”
Section: Liver Demonstrates Marked Enrichment Of Cd4? and Cd8? T Cellmentioning
confidence: 95%
“…The next step will be to study combinations of therapeutic vaccines with other immune interventions and/or direct acting antiviral drugs. For example, PD1/CTLA-4 blockage 44,45 and anti-TIM3 treatment 46 have been shown to restore HCV-specific dysfunctional T cells in vitro, while direct acting antiviral drugs aimed to reduce viral load result in reduced production of viral mutants as well as a decreased T-cell exhaustion. 47 Combined treatment of a potent HCV-specific vaccine with immune interventions and/or direct acting antiviral drugs will hopefully result in de novo HCV-specific T cells and restoration of existing dysfunctional T cells resulting in a better prognosis in patients at various stages of HCV infection.…”
Section: Figure 3 Induction Of Hepatitis C Virus (Hcv)-specific Cytotmentioning
confidence: 99%
“…HCV-specific CD8 + T cells in the peripheral blood of patients have impaired proliferative capacity that is associated with, and reversed by antibody blockade of the inhibitory molecule programmed cell death protein 1 (PD-1) both in vitro [82,86,87] and in vivo [88]. Importantly, PD-1 and other markers of functional exhaustion (such as Tim3, 2B4 and lag3) and apoptosis are further upregulated on intrahepatic T cells [82,89]. A recent publication indicates that epigenetic modification of the PD-1 gene (PDCD1) regulatory element is critical to CD8 + T cell exhaustion and memory development [90].…”
Section: Immunology Of Viral Hepatitis Cmentioning
confidence: 99%